12‐Year Use of a Digital Reference Library (VitalBook) at a U.S. Dental School: Students' and Alumni Perceptions. Issue 10 (1st October 2017) - Spielman, Andrew I.; Maas, Elizabeth; Eisenberg, Elise S.
Abstract : Digital textbooks are being used to reduce production and storage costs of printed copies, enhance usage, and include search capabilities, but the use of digital texts is not universally accepted. In 2001, the New York University College of Dentistry introduced a digital reference library, the VitalBook. Beginning in 2005, the college annually surveyed senior students and, from 2012, also surveyed alumni on their opinions and extent of use of the VitalBook. The aim of this study was to evaluate 12 years of students' perspectives and three years of alumni perspectives on the value of the VitalBook to their dental educational experience. Students were asked how frequently they used the VitalBook, if it was a good investment, if they would use it after graduation, and if they would recommend it to others. Alumni were asked the last three questions. This study reports the results from 4, 105 students over 12 years (average response rate 95.3%) and 184 alumni over three years (average response rate 17.4%). The results indicated that students used the VitalBook on average 24% of their study time, but they were split regarding the other questions. The majority opinion in 2005 was negative on all questions. These opinions shifted to become more favorable to a peak in 2010, but declined since then to a more negative overall view of the VitalBook. A split opinion among students continued through 2016, with fewer recommending it although more considered it a good investment with plans to use it after graduation. Alumni mirrored their responses as students. These results suggest that, as more flexible and dynamic digitized reference systems emerge, the use of student‐paid traditional digitized textbooks may become an even less favored choice.